PSYCHOLOGICAL ASPECTS OF LABOR SAFETY - Котенко, Олег; Васильченко, Александра (SWorldJournal, 2021)
TThe article discusses the psychological causes of accidents arising in the course of work. Psychological factors that increase the propensity of people to accidents are considered. Also considered the types of professional suitability and analyzed the ps